PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT CITRA MANDIRI DISTRIBUSINDO - Herman; Syaifullah (LPPM Universitas Putera Batam, 2021)
The motive on this thesis is to determine the effect of service quality and product quality on purchasing decisions at PT Citra Mandiri Distribution. This study refers to Slovin's theory for data sampling with a margin of error of 5% from a population of 165, so the number of samples is 117 respondents at PT Citra Mandiri Distribution. The data collection method uses a questionnaire. Check the data using validation and reliability, data analysis used using multiple linear regression and coefficient of determination analysis (R2), with 2 hypothesis testing t test and F test which process uses SPSS version 26 software. The results of the coefficient of determination in the study shows that there is a correlation between service quality and product quality with a purchase decision variable of 64.7%. The results of multiple linear regression test of service quality variables have an effect of 18.1% on purchasing decisions and product quality have an effect of 25% on purchasing decisions. The calculated F value on the dependent variable is fully larger than F table which means that the service quality and product quality variables have a positive and significant effect on buying decision. Keywords: Product Quality; Purchasing Decisions; Service Quality.